Pseudoprogression manifesting as recurrent ascites with anti-PD-1 immunotherapy in urothelial bladder cancer. Issue 1 (4th April 2018) - Sweis, Randy F.; Zha, Yuanyuan; Pass, Lomax; Heiss, Brian; Chongsuwat, Tara; Luke, Jason J.; Gajewski, Thomas F.; Szmulewitz, Russell
Abstract : Background: Immunotherapies targeting the PD-1 checkpoint pathway have recently gained regulatory approval in numerous cancer types. With the widespread use of immune checkpoint therapies, varying patterns of responses and immune-related adverse events are being observed. Case Presentation: In this case, we highlight a patient who developed recurrent, large-volume ascites, while simultaneously having a 49% reduction in peritoneal tumor lesion size by RECIST criteria. Sampling of the fluid revealed high levels of IL-6 and IL-15. Cytology revealed no malignant cells on 4 separate paracenteses over a period of 6 weeks. Cell counts revealed that 45% of cells were lymphocytes, and further analysis was performed by fluorescence-activated cell sorting (FACS). The majority of lymphocytes were CD8 +, of which 78% were PD-1 + and 43% were HLA-DR + indicating an activated phenotype. Conclusions: In summary, treatment with anti-PD-1 therapy may result in pseudoprogression manifested by ascitic fluid accumulation due to the influx of activated T cells. Since worsening of ascites is typically associated with disease progression, it is important to consider the possibility of pesudoprogression in such patients undergoing therapy with immune checkpoint inhibitors.